Coconut productivity in the Caribbean: Relational value chains in traditional farming - Silvia Nenci; Carlo Pietrobelli; Marina De Angelis; Hernan Manson (ZBW - Leibniz Information Centre for Economics, 2023)
In this paper, we exploit the new evidence derived from two original farm-level surveys in Jamaica and Guyana, to deepen our understanding of coconut production in the Caribbean region. We innovate on more traditional studies as we include into the analysis not only farm-level variables, but also some characteristics of the communities where farmers operate, the support they obtain from local and foreign organizations, and the organization of the value chain, in particular the relationships they develop with agents and buyers. Our analysis shows that the type of workforce, whether occasional or permanent, and the existence of an irrigation scheme influence coconut productivity in Guyana and Jamaica. Primary education contributes to productivity to a larger extent than higher education. Support from organizations, both international and the Coconut Industry Board is also positively associated to productivity. In addition, selling to agents offers a positive productivity premium, probably due to the opportunity agents offer to get relevant information and technology. Thus, traces of a simple "relational" value chain, with a positive and useful role for interactions and exchange of tacit knowledge from buyers and agents, emerge from our study.
Keywords: D24; O13; Q12; O54; 330; Coconut; productivity; Relational value chains; Caribbean countries